Frequency of Meningitis in Children Presenting with Febrile Seizures at Ali- Asghar Children’s Hospital - TAVASOLI, Azita; AFSHARKHAS*, Ladan; EDRAKI, Abdolmajid (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Tavasoli A, Afsharkhas L, Edraki A. Frequency of Meningitis in Children Presenting with Febrile Seizure in Ali-Asghar Children’s Hospital. Iran J Child Neurol. 2014 Autumn; 8(4):51-56. Abstract Objective Febrile seizures (FS) are the most common type of childhood seizures, affecting 2–5% of children. As the seizure may be the sole presentation of bacterial meningitis in febrile infants, it is mandatory to exclude underlying meningitis in children presenting with fever and seizure. To determine the frequency of meningitis in children with FS and related risk factors, the present study was conducted at Ali-Asghar Children’s Hospital. Materials & Methods The records of children aged from 1-month–6 years of age with fever and seizure admitted to the hospital from October 2000–2010 were studied. The charts of patients who had undergone a lumbar puncture were studied and cases of meningitis were selected. The related data was collected and analyzed with SPSS version 16. Results A total of 681 patients with FS were known from which 422 (62%) lumbar punctures (LP) were done. Meningitis (bacterial or aseptic) was identified in 19 cases (4.5%, 95% CI 2.9–6.9 by Wilson- Score internal) and bacterial meningitis in 7 (1.65%, 95% CI 0.8–3.3). None of the patients with bacterial meningitis had meningeal irritation signs. Complex FS, first attack of FS, and impaired consciousness were more common in patients with meningitis when compared to non- meningitis patients. Conclusion Meningitis is more common in patients less than 18 months presenting with FS; however, complex features of seizures, first attack of FS, or impaired consciousness seem significant risk factors for meningitis in these children and an LP should be considered in this situation. References Kimia A, Ben-Joseph EP, Rudleo T, et al. Yield of lumbar puncture among children who present with their first complex febrile seizure. Pediatrics.2010; 126: 62-69. Hom J, Medwid K, The low rate of bacterial meningitis in children, ages 6 to 18 months, with simple febrile seizures. AcadEmerg Med 2011; 18(11):1114-1120. Fetveit A. Assessment of febrile seizures in children. Eur J Pediatr 1998; 167(1); 17-27. Subcommittee on Febrile Seizures. Febrile seizures: Guidelines for the neurodiagnostic evaluation of the child with a simple febrile seizure. Pediatrics 2011; 127(2):389-394. Rosman NP. Evaluation of the child who convulses with fever. Pediatr Drugs 2003; 5(7):457- 461. Dubos F, De la Rocque F, Levy C et al. Sensitivity of the bacterial meningitis score in 889 children with bacterial meningitis. J Pediatr 2008; 152:378-382. Nigrovic LE, Kuppermann N, Macias CG, et al. Clinical prediction rule for identifying children with cerebrospinal fluid pleocytosis at very low risk of bacterial meningitis. JAMA 2007; 297(1):52-60. American Academy of Pediatrics. Provisional Committee on quality improvement, Subcommittee on Febrile Seizures. Practice parameter: the neurodiagnostic evaluation of the child with a first simple febrile seizure. Pediatrics 1997; 769-772. Najaf-Zadeh A, Dubos F, Hue V, et al. Risk of bacterial meningitis in young children with a first seizure in the context of fever: a systematic review and meta- analysis. PLoS One. 2013; 8(1):e55270. Doi: 10. 1371/journal. pone.0055270. Owusu-Ofori A, Agbenyega T, Ansong D, et al. Routine lumbar puncture in children with febrile seizures in Ghana: should it continue? International Journal of Infectious Diseases 2004; 8:353-361. Kimia AA, Capraro AJ, Hummel D, Johnston P, Harper MB. Utility of lumbar puncture for first simple febrile seizure among children 6 to 18 months of age. Pediatrics 2009; 123(1): 6–12. Shaked O, Pena BM, Linares MY, Baker RL. Simple febrile seizures: are the AAP guidelines regarding lumbar puncture being followed? Pediatr Emerg Care 2009; 25(1):8-11. Seltz LB, Cohen E, Weinstein M. Risk of bacterial or herpes simplex virus meningitis/encephalitis in children with complex febrile seizures. Pediatr Emerg Care 2009;25(8): 494–497. Casasoprana A, Hachon Le Camus C, Claudet l, et al. Value of lumbar puncture after a first febrile seizure in children aged less than 18 months. A retrospective study of 157 cases. Arch Pediatr, 2013. Pil: S0929-693X (13)00238-8. Kwang SK. Bacterial meningitis beyond the neonatal period. In: Cherry JD, Harrison GJ, Kaplan Sh L, Steinbach W.J, Hotez PJ, eds. Feigin and Cherry’s textbook of pediatric infectious diseases: Philadelphia, Elsevier, Saunders.2014.P:425-472. Ehsanipour F, Khodapanahandeh F, Aslani Z. The prevalence of meningitis in children with febrile seizure hospitalized at Hazrat Rasoul hospital (1997-2002). Journal of Iran University of Medical Sciences 2004; 44;907-912. Al-Eissa YA. Lumbar puncture in the clinical evaluation of children with seizures associated with fever. PediatrEmerg Care 1995; 11(6):347-350. Ghotbi F, Shiva F. An assessment of the necessity of lumbar puncture in children with seizure and fever. J Pak Med Assoc 2009; 59(5):292-295. Tinsa F, EL GhrbiA, NcibiN, et al. Role of lumbar puncture for febrile seizure among infants under one year old. Tunis Med 2010; 88(3): 178-183. Joshi Bataloo R, Rayamaihi A, Mahaseth C. Children with first episode of fever with seizure: is lumbar puncture necessary? JNMA J Nepal Med Assoc 2008;47(171):109-112. Carrol W, Brookfield D. Lumbar puncture following febrile convulsion. Arch Dis Child 2002; 87:238-240. Laditan AA. Analysis of the results of routine lumbar puncture after a first febrile convulsion in Hofuf, Al-Hassa, Saudi Arabia. East Afr Med J 1995;72:376- Rossi LN, Brunelli G, Duzioni N, et al. Lumbar puncture and febrile convulsion. Helv Pediatr Acta 1986; 41(1-2):19-24. Mikati M A. Febrile seizures. In: Behrman RF, Kliegman RM, Jenson HB. (editors). Nelson Textbook of Pediatrics. 19th ed. Philadelphia: Saunders. 2011. Pp: 2017-19.